Predicted Operando Polymerization at Lithium Anode via Boron Insertion - Liu, Yue; Yu, Peiping; Sun, Qintao; Wu, Yu; Xie, Miao; Yang, Hao; Cheng, Tao; Goddard, William A (ACS energy letters, 2021)
Concentrated dual-salt/ester systems have been demonstrated as an effective method in regulating the solid electrolyte interphase (SEI) formation that facilitates the long-term cycling stability of lithium metal batteries (LMBs). However, the atomic mechanism of the dual-salt enabling the stable SEI formation remains unclear. In this work, a hybrid scheme, combining ab initio and reactive force field methods (HAIR), is employed to investigate the initial reaction of SEI formation by monitoring 1 ns molecular dynamics (MD) simulation. The simulation results reveal that lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) is subject to a sacrificial decomposition to protect lithium difluoro(oxalato)borate (LiDFOB) from being over-reduced by Li metal. The boron (B) released from LiDFOB can initiate a polymerization reaction by cutting the C–O bond. Such unexpected reaction turns dimethoxyethane (DME), a previously considered stable solvent, into a radical that can facilitate the propagation of polymerization. These insights from simulation provide atomic understanding about the complex reaction in SEI.